2016
DOI: 10.3389/fpls.2016.00589
|View full text |Cite
|
Sign up to set email alerts
|

Increased Virulence in Sunflower Broomrape (Orobanche cumana Wallr.) Populations from Southern Spain Is Associated with Greater Genetic Diversity

Abstract: Orobanche cumana Wallr. (sunflower broomrape) is a holoparasitic weed that infects roots of sunflower in large areas of Europe and Asia. Two distant O. cumana gene pools have been identified in Spain, one in Cuenca province in the Center and another one in the Guadalquivir Valley in the South. Race F has been hypothesized to have arisen by separate mutational events in both gene pools. In the Guadalquivir Valley, race F spread in the middle 1990’s to become predominant and contained so far with race F hybrids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 29 publications
1
30
0
3
Order By: Relevance
“…Current findings support the reported allelopathic influence of rice on the seed germination of sunflower broomrape and clover broomrape [27]. The sunflower and Egyptian broomrape seeds may contain receptors specifically designed to receive biochemical signals and respond to it depending on the perception [31,32]. Chemical interaction may not entirely be entitled to demonstrate this situation as the possible contribution of certain physical factors, such as seed coat structure, which can alter the reception and perception of a certain biochemical or stimulus.…”
Section: The Differential Germination Indicates a Genetic And Biochemsupporting
confidence: 74%
“…Current findings support the reported allelopathic influence of rice on the seed germination of sunflower broomrape and clover broomrape [27]. The sunflower and Egyptian broomrape seeds may contain receptors specifically designed to receive biochemical signals and respond to it depending on the perception [31,32]. Chemical interaction may not entirely be entitled to demonstrate this situation as the possible contribution of certain physical factors, such as seed coat structure, which can alter the reception and perception of a certain biochemical or stimulus.…”
Section: The Differential Germination Indicates a Genetic And Biochemsupporting
confidence: 74%
“…In the report of Molinero-Ruiz et al [30] races commonly found in Spain were E and F. Recently, spreading of broomrape was recorded in the northern parts of Spain with a source in the Guadalquivir Valley, race F being the most virulent one [31]. At the same time, a change in broomrape virulence is also taking place in Spain, observed as broomrape occurrence on hybrids with resistance to race F, and labelled with sign G GV [3]. This event was peculiar because a susceptible reaction of inbred lines DEB-2 and P-96 was lacking although resistance in commercial hybrids was overcome.…”
Section: Current Racial Status Of Broomrape World-widementioning
confidence: 99%
“…Single point mutation was reported as a probable cause of race F emergence [38]. Gene flow from O. cumana from wild Asteraceae was also indicated as the potential source of virulence diversity, as well as the admixture of the local populations [3,39]. The mechanisms to overcome resistance may already exist in some broomrape individuals within a population [40].…”
Section: Current Racial Status Of Broomrape World-widementioning
confidence: 99%
See 2 more Smart Citations